Strategi Pemasaran dan Peningkatan Kualitas Pelayanan Untuk Meningkatkan Kepuasan Pelanggan Pada Agen Travel Umroh dan Haji Tomboati Malang - Fairuz Arsy Aribah Emeralda Fitri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study specifically investigates the implementation and synergistic impact of digital marketing strategies and service quality improvements on customer satisfaction at the Toureligi Umrah and Hajj travel agency in Jember. A descriptive qualitative research method was applied in-depth through semi-structured interviews with marketing managers, customer service staff, and participant observation of interactions in the office and on digital platforms. Data sources were verified through triangulation to ensure the validity of the findings. The results revealed that Toureligi's marketing strategy, which focuses on educational content on social media (such as Instagram and Facebook) and leverages pilgrim testimonials in the form of vlog videos, proved effective in building perceptions of credibility and emotional value among potential customers. Furthermore, service quality analysis identified that the dimensions of empathy (personalized approach in consultations), reliability (consistency of packages and facilities), and assurance (certification and clarity of procedures) were key pillars in building loyalty. However, critical findings revealed gaps in responsiveness, particularly in digital services, such as slow chat responses outside of business hours and a lack of integrated information systems. The study's conclusions confirm that improving customer satisfaction at Toureligi Jember relies not only on a massive marketing strategy but also on the ability to correlate it with concrete improvements in service quality, particularly in closing the digital responsiveness gap. The strategic implication of this study is the need to develop an integrated Customer Relationship Management (CRM) system to align marketing expectations with the reality of service experiences, in order to maintain long-term customer loyalty.